Kajian Putusan Pada Perkara Hadhanah Ditinjau Dari Undang-Undang Tentang Perlindungan Anak - Herlintoni, Serli (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
Abstract: Decision On The Case Study Ofhadhanah Viewed From The Law On The Protection Of Children. Fiqh scholars agree that the laws of caring for and educating children is mandatory, because if it is not cared for and well educated, will reflect badly on themselves, can even lead to losing their lives. In the case ofhadhanah decision No.34 / Pdt.G / 2014 / PA.Crp and No. 16 / Pdt.G / 2015 / PA.Crp hadhanah has granted to the mother, but the basic of its legal consideration is vary. These Differences will be recorded, analyzed philosophically and normatively. This paper will examine how the consideration of judges in deciding cases ofhadhanah No. 34 / Pdt.G / 2014 / PA.Crp and No. 16 / Pdt.G / 2015 / PA.Crp terms of Act No. 23 of 2002 on Protection of Children and legal settings. This research is a normative legal research with qualitative methods in the form of literature studies. The approach used in this study isstatute approach and case approach. Data were analyzed using comparative analysis. The results of this study indicate that in case the decision ofhadhanah No. 34 / Pdt.G / 2014 / PA.Crp and case No. 16 / Pdt.G / 2015 / PA.Crp, judges tend to pay less attention to consideration of the regulations to the Act No. 23 of 2003 on Protection of Children Jo No. 35 of 2014 regarding Child Protection. Legal arrangements in the settlement of hadhanah isverzet, appeal, and need to be applied mediation and dwangson that the defendant is willing to fulfill his promise.